Anaerobic digestion of perennial ryegrass prepared by cryogenic freezing versus thermal drying methods, using contrasting in vitro batch digestion systems - Nolan, P.; Luostarinen, S.; Doyle, E. M.; O'Kiely, P. (Pergamon-Elsevier Science Ltd, 2016)
At present no complete standard methodology is adhered to when utilising biomethane potential (BMP) tests. This can limit the use of results as relationships observed may be confined to each specific BMP test. The purpose of this study was to investigate the specific CH4 yields of a range of grasses and corresponding silages, via cryogenically frozen (-196 degrees C) and thermal dried (40 degrees C) sample preparation methods, using two contrasting in vitro batch anaerobic digestion tests. The manual BMP test (MBMP) yields ranged from 180 to 285 and 172-264 L CH4 kg(-1) volatile solids (VS) for the cryogenically frozen and thermal dried preparation methods, respectively. The corresponding automated BMP test (AMPTS) yields ranged from 329 to 346 and 287-330 L CH4 kg(-1) VS. Overall treatment rankings in the AMPTS did not match the rankings observed in the MBMP. However, within the category of silage the rankings were similar for both tests. Since most of the grassland biomass intended for anaerobic digestion is likely to be stored as silage, it is preferable to use cryogenically frozen and milled samples, rather than thermal dried and milled samples when assessing methane potential of silage in a small-scale BMP test.
Keywords: harvest management; grass silage; preparation method; representative sampling; biomethane potential test; methane yield; biogas production; grass-silage; biomethane; pretreatment; crops